Calvo wages in a search unemployment model - Vincent Bodart; Olivier Pierrard; Henri R. Sneessens (Institute for the Study of Labor (IZA), 2006)
RBC models with search unemployment and wage renegotiation generate too much wage volatility and too stable unemployment rate. Shimer (2004) shows that it is possible to reproduce a volatility of unemployment similar to that observed in actual economies by imposing full real wage rigidity. We use a similar model but with Calvo wage contracts and we obtain a microfounded equation of real wage rigidities. The models with full wage flexibility or full wage rigidity are obtained as particular cases. We show that a contract length of about six quarters fits best the observed cyclical properties of wages and unemployment.
urn:nbn:de:101:1-2008050291
Keywords: 330